ANALISIS PEMBUATAN VIDEO PEMBELAJARAN MENGGUNAKAN APLIKASI CAMTASIA DAN WONDERSHARE FILMORA DALAM PEMBELAJARAN ONLINE PADA SMK AR-RAHMAN MEDAN - rikky simanjuntak; Muhammad Daliani; Nilam Sari; Vera Ompusunggu (Universitas Quality, 2021)
Based on the Circular from the Minister of Education and Culture Number: 36962/MPK.A/HK/2020 dated March 17, 2020 regarding